2012
DOI: 10.1111/j.2041-1294.2012.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fracture of Glass: Past, Present, and Future

Abstract: This paper presents a summary of brittle fracture in silicate glasses. In it is discussed our current knowledge of the fracture mechanisms, what studies are ongoing, and what still remains unknown. The paper presents a historical perspective of the research into glass fracture including an annotated bibliography of key publications. Several key points include the susceptibility of silicate glasses to environmentally enhanced crack growth, the quantitative nature of the markings left on the fracture surface by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 75 publications
(128 reference statements)
2
8
0
Order By: Relevance
“…However, a quantitative description of the underlying mechanisms of crack propagation, critical to the further development of crack-resistant glasses, is presently unavailable (Wondraczek et al, 2011;Freiman, 2012). This is largely due to the fundamental nature of cracking as it occurs in the broad group of brittle oxides, and especially in glassy silicates: crack propagation reflects a complex and, as of yet, not fully understood interplay of chemical and physical interactions (Ciccotti, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, a quantitative description of the underlying mechanisms of crack propagation, critical to the further development of crack-resistant glasses, is presently unavailable (Wondraczek et al, 2011;Freiman, 2012). This is largely due to the fundamental nature of cracking as it occurs in the broad group of brittle oxides, and especially in glassy silicates: crack propagation reflects a complex and, as of yet, not fully understood interplay of chemical and physical interactions (Ciccotti, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Scientists also evidence that the environ mental pH alters the glass' stress corrosion cracking behavior [12,69]. As pointed out above, several reviews address these topics [4,150]. Despite extensive research, there is a distinct lack of systematic studies concerning the relationship between the chemical composition of glasses and the stress corrosion cracking behavior.…”
Section: Presentation Of Sbn Stress Corrosion Cracking Resultsmentioning
confidence: 99%
“…A similar interstitial network modifier is sodium, for which some data relating concentration and glass strength exists. Investigated by Kennedy et al [19] and summarised by Freiman [20], it was found that increasing the concentration of sodium in silica glass produced an increase in fracture toughness. It was postulated that this may be related to changes in straining or bending of Si-O bonds, thus influencing the size of a so-called process zone near the crack tip where elastic fracture mechanics may no longer apply.…”
Section: Chemical Surface Changesmentioning
confidence: 99%